Fiscal regimes in resource dependent African states: a political economy game - Temitope J. Laniran (African Governance and Development Institute (AGDI), 2017)
Policy reform debates in African economies often focus on poverty alleviation programs, liberalisation of trade and market and social service provisions. These reforms are heavily dependent on funding from either foreign sources or natural resource wealth, accompanied with concessions from the East and conditionality laden Western sources. They rarely optimally explore the internal fiscal revenue sources of their economy and as such undermines the fiscal prowess of their economies. Despite the less desirable situation, most resource-dependent African economies have found themselves, the elite political class in these countries still engage in wasteful expenditure pattern. The question of demand for accountability and good governance is rather ambiguous to the majority of the electorate as there is often a weakfiscal contract between them and the elite political class. The acknowledgement of this gives politicians an ïncentiveẗo perpetuate corrupt activities which enrich the elite class at the expense and well-being of the masses and widens the inequality gap. This scenario is rather worse off in natural resource-endowed developing economies. The elite classis faced with a game-like situation, where the payoffs can either be beneficial to the elite class at the expense of the electorate or beneficial to the electorate at the expense of the elite class.This study expands the discussion on how an effective fiscal regime can help improve accountability and welfare of citizens in natural resource-endowed African states.
Keywords: D72; O10; Q30; 330; Accountability; Natural Resources; Fiscal Regimes